Diabetes is associated with lower tuberculosis antigen-specific interferon gamma release in Tanzanian tuberculosis patients and non-tuberculosis controls. (May 2014) - Faurholt-Jepsen, Daniel; Aabye, Martine Grosos; Jensen, Andreas Vestergaard; Range, Nyagosya; Praygod, George; Jeremiah, Kidola; Changalucha, John; Faurholt-Jepsen, Maria; Jensen, Lotte; Jensen, Signe Marie; Krarup, Henrik; Ravn, Pernille; et al.
Abstract Background: Diabetes is increasingly common in TB endemic regions and plays a role as a possible risk factor for increased progression from latent TB infection (LTBI) to active TB disease. Although the pathophysiological mechanisms are not fully understood, the immune system is weakened in diabetes patients and therefore the validity of interferon gamma release assays (IGRA) may be compromised. The aim of the present study was to assess the association between diabetes and Mycobacterium tuberculosis (Mtb) antigen-specific interferon gamma (IFN-γ) release in a TB endemic area among culture-confirmed TB patients and non-TB controls. Methods: Culture-confirmed pulmonary TB patients (n = 187) and healthy non-TB neighbourhood controls (n = 190) from Mwanza, Tanzania were tested for the presence of circulating T cells recognizing Mtb antigens using an IGRA. The diabetes status of all participants was assessed using a standard oral glucose tolerance test. The impact of diabetes on the performance of the IGRA was estimated using robust linear and logistic regression. Results: Compared to normal glucose tolerance, diabetes was associated with reduced levels of Mtb-specific IFN-γ. Increasing levels of fasting blood glucose (B − 0.3, 95% confidence interval − 0.6 to − 0.03, p = 0.033) was negatively associated with IFN-γ. Although TB patients had higher specific and lower unspecific mitogen IFN-γ responses compared to non-TB controls, the association between diabetes and IFN-γ did not depend on TB status. Conclusion: Diabetes is associated with lower levels of Mtb antigen-specific IFN-γ, and the validity of IFN- γ tests for LTBI may be questionable in individuals with diabetes.